Dynamics of Fertilizer Subsidy Implementation: A Case Study of Agricultural Policy in Indonesia - Fatimah, Astri Siti; Muhafidin, Didin (International Journal of Science and Society, 2024)
This study explores the dynamics of fertilizer subsidy implementation in Indonesia, focusing on its impact on agricultural policy and practice. With the critical role of subsidies in supporting the agricultural sector, this research aims to provide a comprehensive analysis of their implementation and effectiveness. Utilizing a systematic literature review methodology, the study synthesizes data from a wide range of academic journals, government reports, and policy analyses. The findings highlight the complexities involved in the implementation process, including issues related to policy design, distribution mechanisms, and the actual impact on farmers' productivity and sustainability practices. The study identifies key challenges such as bureaucratic inefficiencies, misallocation of resources, and unintended consequences on smallholder farmers. Additionally, it examines the implications of these subsidies for sustainable agricultural development and the economic resilience of rural communities in Indonesia. The conclusion offers critical reflections on policy recommendations and future directions for optimizing the effectiveness of fertilizer subsidies in enhancing sustainable agricultural growth.